2009
DOI: 10.5694/j.1326-5377.2009.tb02618.x
|View full text |Cite
|
Sign up to set email alerts
|

The PACT Project: improving communication at handover

Abstract: Objective: To describe and evaluate the PACT (Patient assessment, Assertive communication, Continuum of care, Teamwork with trust) Project, aimed at improving communication between hospital staff at handover. Design, setting and participants: The PACT Project was conducted between April and December 2008 at a medium‐sized private hospital in Victoria. Action research was used to implement and monitor the project, with seven nurses acting as a critical reference group. Two communication tools were developed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 3 publications
2
47
1
1
Order By: Relevance
“…The mechanisms of improving referral effectiveness in this situation are likely to be a combination of all three. Other studies have suggested that use of an SBAR minimum information tool helps staff ‘know what they should say’ when making referrals 15. Although we expected to show improvement in knowledge (presence of expected critical data to be transferred during referral), this was not the case.…”
Section: Discussioncontrasting
confidence: 58%
“…The mechanisms of improving referral effectiveness in this situation are likely to be a combination of all three. Other studies have suggested that use of an SBAR minimum information tool helps staff ‘know what they should say’ when making referrals 15. Although we expected to show improvement in knowledge (presence of expected critical data to be transferred during referral), this was not the case.…”
Section: Discussioncontrasting
confidence: 58%
“…Importance and relevance of capturing information related allergies, comorbidities, assessment of pain, neurological monitoring, and aspects to be documented under the plan of care need to be incorporated as a regular part of continuing education program. An audit to look for reduced number of incidents related to communication failures is essential for long-term evaluation of patient outcomes[3] and thus, provide safe and quality care to patients.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Studies indicate that use of structured handoffs will improve the quality of patient handover. [345] Hands off is the transfer of responsibility and accountability of a patient, from one nurse to another[6] either during shift handover or transfers of the patient from one department to the other.…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature review in chart note writing and EHR documentation functionalities, five categories were created: EHR-writing competence (21), EHR-reading competence (19, 21), and EHR-writing preference in terms of input format (typing vs. check boxes) (16, 26), EHR-reading preference in terms of output format (narrative vs. bullet points) (27), and EHR-reading preference (succinct vs. lengthy) (28). EHR-writing competence includes an ability to create thorough and complete notes, using an appropriate form in a timely manner.…”
Section: Methodsmentioning
confidence: 99%